An improved reliability model for Si and GaN power FET. (February 2018) - Golan, Gady; Azoulay, Moshe; Avraham, Tsuriel; Kremenetsky, Ilan; Bernstein, Joseph B.
Abstract: The existing standard reliability models for power devices are not satisfactory and they fall short of predicting failure rates or wear-out lifetime of semiconductor products. This is mainly attributed to two reasons; the lack of a unified approach for predicting device failure rates and the fact that all commercial reliability evaluation methods relay on the acceleration of one dominant failure mechanism. Recently, device reliability research programs are aimed to develop new theoretical models and experimental methods that would result a better assessment of the device lifetime as well as point out on the dominating failure mechanism for particular operating conditions. A new model, named Multi failure mechanism, Overstress Life test (MOL) has been introduced and posed a better understanding of the dominating failure mechanisms under various stressed conditions in advanced FPGA devices (for 45 and 28 nm technologies). In this work we present, for the first time, the implementation of the MOL model to investigate the reliability of silicon power MOSFET and GaN power FET devices. Both, LTSpice simulation and experimental data are presented for a test circuit of a ring oscillator, based on CMOS-FET, NMOS-FET, PMOS-FET and N-channel e-GaN FET. The monitored data was acquired in-situ in form of the ring frequency or Vds values that enabled to assess the lifetime and determine the dominating mechanism during accelerated wearout by temperature, applied bias voltage, thermal cycling, gamma and electron irradiation. Moreover, in the case of GaN devices, RDS-On monitoring circuit has also been operated during thermal cycling of the tested component and the acceleration factor was derived for various operational parameters.